(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
The purpose of this research was to find out the influence of circuit-based ability training on the success of woman football players’ skills. 30-woman footballers from Nirmala College for Women, Coimbatore, were chosen to accomplish the aim of the report. Their age ranged from 18 to 25 years and they were broken into equal classes of 15 each. Group- I was educated in circuits and Group-II served as the control group (CG). The training was offered to the experimental community for eight-week duration of 3 days a week (Monday, Wednesday and Friday). No form of training was provided to the control group besides their regular jobs. The data obtained from the subjects was statistically evaluated with ’t’ ratio to figure out substantial change if any at 0.05 level of trust. The result hypothesised that the kicking and passing of women footballers dramatically improved due to the effect of circuit-based skill training with the disadvantages of position (diet, environment, life style) and prior training, the outcome of the current study agrees with the research results of numerous professionals in the field of sports sciences.